Pollution of Water and Stream Sediments Associated with the Vale De Abrutiga Uranium Mine, Central Portugal - Pinto, M. M. S. C. (2004)
The Vale de Abrutiga uranium deposit, located in Central Portugal near the Aguieira dam reservoir, was surface mined. Low-grade ore and waste rock were deposited on permeable ground, close to the mine, and were not revegetated. A lake has formed in the open pit. Surface waters draining the mine site are acidic, have high conductivity, and high concentrations of U, SO42-, Zn, Fe, Mn, Ra, Cu, Th, and Pb. The groundwater and the water from the reservoir cannot be used for human consumption or irrigation. The sampled waters show higher contaminant concentrations in winter than in summer. Stream sediments have high geoaccumulation indices for U, Fe, Ag, Zn, Cr, Co, and Pb. In general, sediments bordering the dam reservoir have higher metal contents in winter than in summer.